Case Report: Bowel Occlusion Following the Use of Barbed Sutures in Abdominal Surgery. A Single-Center Experience and Literature Review - Stabile, Guglielmo; Romano, Federico; De Santo, Davide; Sorrentino, Felice; Nappi, Luigi; Cracco, Francesco; Ricci, Giuseppe (Frontiers in Surgery, 2021)
Introduction: A high level of surgical ability is required to perform endoscopic knot tying. Barbed sutures help in avoiding this procedure, thus reducing intraoperative time and lowering blood loss and hospitalization time when compared to traditional sutures. Some cases of bowel occlusion following the use of barbed sutures have been described in literature. All of them are characterized by the entanglement of an intestinal loop in wire barbs with bowel occlusion symptoms. Case Presentation: We report two more cases which occurred in our Institute in 2020 and review those which have been reported in the literature by searching on Pubmed, Scopus, and Embase. We used the search terms: “Barbed,” ”Suture,” “Bowel,” and ”Obstruction.” We examined in the literature the surgical procedures, the type of complications, the time to onset of the complications, and the type of barbed suture. Discussion: Twenty-two cases in total were reported in the literature from 2011 to 2020, and bowel complications were largely subsequent to interventions such as hernia surgical repair and myomectomy. In order to take advantage of barbed sutures while minimizing the risk of adverse events, such as intestinal occlusion, some precautions may be considered, such as the shortening of thread tails and use of antiadhesive barriers. Moreover, performing a few stitches backwards when ending the suture might be a useful suggestion. Further studies in this field may be useful in order to assess whether it might be better avoiding barbed suture application on serosal tissues to prevent bowel damage.